2022
DOI: 10.3389/fphys.2022.1053060
|View full text |Cite
|
Sign up to set email alerts
|

Effects of green tea extract treatment on erythropoiesis and iron parameters in iron-overloaded β-thalassemic mice

Abstract: β-Thalassemia is characterized by ineffective erythropoiesis leading to chronic anemia. Thus, increased iron absorption from the duodenum and via blood transfusions is required to maintain normal blood hemoglobin (Hb) levels and iron chelators in the removal of excessive iron. Certain agents are also needed for the improvement of stress erythropoiesis and iron dysregulation. Green tea extract (GTE), which is rich in epigallocatechin-3-gallate (EGCG), is known to possess radical scavenging and iron-chelating ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 83 publications
(97 reference statements)
0
11
0
Order By: Relevance
“…EGCG is also a strong iron chelator and may reduce ROS by binding free iron. Several in vitro and in vivo studies have shown that EGCG treatment can prevent cancer, vascular diseases and neurological disorders 44 - 46 that are associated with iron dysregulation. In our previous study, EGCG decreased iron uptake and retention in N27 cells and prevented against 6-OHDA induced neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EGCG is also a strong iron chelator and may reduce ROS by binding free iron. Several in vitro and in vivo studies have shown that EGCG treatment can prevent cancer, vascular diseases and neurological disorders 44 - 46 that are associated with iron dysregulation. In our previous study, EGCG decreased iron uptake and retention in N27 cells and prevented against 6-OHDA induced neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…This is inconsistent with the results of other studies showing that EGCG acted as a promoter of antioxidant and anti-inflammatory properties by activating Nrf2 and HO-1 exression. 44 , 46 , 47 One reason for this may be that 6-OHDA-induced oxidative stress and inflammatory response could further activate the protein expression of Nrf2, HO-1, and PPARγ, whereas EGCG treatment restored the cells to a level of low oxidative stress and inflammation. Another reason for the discrepancy of our results might be related to the difference of cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the A-value of the colored product was measured at 595 nm against the reagent blank by spectrophotometry. A standard BSA solution (0–500 μg/mL) was used to make a standard graph for the determination of the membrane protein concentration ( Settakorn et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Their studies showed these two mushrooms have great power in chelating iron. Various studies have shown that flavonoid compounds like catechin, quercetin, and naringin can chelate iron ions in iron-overloaded rats 20 22 . Natural chelators and their metabolites are good antioxidants due to their lower toxicity and greater stability than synthetic chelators 23 .…”
Section: The Classification Of Iron Chelatorsmentioning
confidence: 99%